The study of output current in photovoltaics cell in series and parallel connections - Norlinda Binti Mohd Yusof; Annuar Bin Baharuddin (International Journal of Technology, Innovation and Humanities, 2020)
Photovoltaic cells in solar is an electrical device that converts the energy of light directly into electricity by the photovoltaic effect.  In this work, series and parallel arrangement of the photovoltaic cells in solar system were investigated over a range of voltage, current and power. The data obtained were statistically analyzed to predict the optimal energy conservation of photovoltaic cells and finally experiments were conducted for verification.  The experiment designed is to observe the output current in both series and parallel PV cells arrangement with the output current of the three sets of photovoltaic cells (PV), with a minimum input supply of 18.7V DC and 8.82A respectively. Digital multimeter and current clamp meter are the main instruments used to measure the parameters in the experiment. The parameters for the circuit are analyzed based on the voltage, current, power and the efficiency of the system. Indeed, the output current and voltage for both arrangements were able to be used to derive the efficiency of the system and showed good agreement with the results from the preliminary observation.  It is shown that the efficiency of parallel arrangement is higher compare to the series. Therefore, considerable investigation towards the types of arrangements is of great importance since it can determine the better system efficiency when there are any faulty panels